Motivation from People Closest to Local and Non-Local Students Against Determining Physics Identity in Analytical Mechanics Courses - Pitono, Anindita Putri Canina; Ramadhani, Motik Mutiara; Setiaji, Bayu (Impulse: Journal of Research and Innovation in Physics Education, 2024)
This study aims to find out more about the influence of motivation from people closest to them on the formation of physics identity, especially for local students (living in D.I. Yogyakarta) and non-local (from outside D.I. Yogyakarta), on the results of analytical mechanics courses. This qualitative descriptive study uses a descriptive-analytical approach based on the results of interviews with 8 sample respondents representing local students (living in D.I. Yogyakarta) and non-local (coming from outside D.I. Yogyakarta) in the Physics Education Department, Yogyakarta State University. All respondents have been able to describe their physics identity, accompanied by strong motivation from people closest to them, including themselves, without any differences between local and non-local students regarding the final results of analytical mechanics. After knowing the results of this study, it is hoped that students can further develop their physics identity so that it has an impact on the final grades of the courses they take.